Observations of Evolution‐Type Band‐Like Structures of F Region Irregularities. Issue 2 (23rd February 2019) - Meng, Xing; Fang, Hanxian; Li, Guozhu; Weng, Libin; Wang, Sicheng
Abstract: Generally, equatorial spread‐ F (ESF) irregularities initiated at the bottom of the ionospheric F region and manifested as plume structures with an altitude extent more than 50 km in the RTI (range‐time‐intensity) plot. By using the Fuke and Sanya VHF radars located at low latitude of China, evolution‐type band‐like structures of ESF irregularities were observed near local sunset. One interesting aspect is that the ESF band‐like structures initially appeared at high altitudes more than 400 km and then uplifted to higher altitude without zonal propagation. The lifetime of these ESF band‐like structures, with a similar pattern in the RTI plot for each beam of radar, is less than 25 min. The band‐like structures of F region irregularities were observed with big Doppler velocities and narrow spectral widths. During the presence of ESF band‐like structures, apparent amplitude scintillations (S4 > 0.2), total electron content (TEC) fast fluctuations (ROTI > 1), and range‐type spread F were detected. Possible mechanisms responsible for the initial generation of band‐like ESF irregularities at high altitude are discussed. Key Points: Evolution‐type band‐like irregularity structures with short lifetime (less than 25 min) were detected by Hainan VHF radars The band‐like irregularity structures originated near local sunset above 400 km and almost did not show zonal propagation The band‐like irregularities were accompanied by spread echoes recorded by ionosonde indicating that they are related to ESF